2007
DOI: 10.1108/ohi-01-2007-b0005
|View full text |Cite
|
Sign up to set email alerts
|

Mass Housing: Residents Satisfaction with their Housing and Environment

Abstract: It is often necessary to assess the satisfaction of the house users with the house environment, in other words the compliance of the environment with their expectations, needs and goals. The quality of residence and environment affects the general life satisfaction of the human. If the residents are satisfied with their residences and residence environments, this influences their psychological and physical health and these all together have an impact on the structure of the society. Therefore if the variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…They found that, together with household amenities, recreational and educational facilities are significant predictors of residential satisfaction. Berköz and Kellekçi (2007) studied mass housing environments in Istanbul's Bahcesehir neighborhood. They found that accessibility to various functions and the city center, environmental features and security, neighbor relationships and the appearance of the housing environment are factors affecting residential satisfaction (Berköz et al, 2009).…”
Section: Neighborhood Qualitiesmentioning
confidence: 99%
“…They found that, together with household amenities, recreational and educational facilities are significant predictors of residential satisfaction. Berköz and Kellekçi (2007) studied mass housing environments in Istanbul's Bahcesehir neighborhood. They found that accessibility to various functions and the city center, environmental features and security, neighbor relationships and the appearance of the housing environment are factors affecting residential satisfaction (Berköz et al, 2009).…”
Section: Neighborhood Qualitiesmentioning
confidence: 99%
“…Konut memnuniyetine yönelik bir diğer çalışmada da kullanıcının yaş, gelir düzeyi, çocuk sahipliliği, eğitim düzeyi gibi demografik özellikleri ve altyapı, oda sayısı, büyüklük gibi konutun fiziksel özellikleri önemli göstergeler olarak tanımlamaktadır (Galster ve Hesser, 1981). Benzer şekilde, konut büyüklüğü (Cho, 2020;Li vd., 2019;Huang ve Du, 2015;), konut kalitesi (Cho, 2020;Ciorici ve Dantzler, 2019), yönetim ve hizmet (Cho, 2020) , komşularla sosyal ilişkiler (Berkoz ve Kellekci, 2007;Grange ve Yau, 2020) gibi göstergelerin de konut sakinlerinin memnuniyetini etkilediği belirtilmektedir.…”
Section: Kullanıcı Memnuniyetini Etkileyen Göstergelerin Belirlenmesiunclassified
“…In recent years, numerous studies have reported on housing environment dimensions and their impact on residents’ satisfaction and their happiness (Pishgahi and Partovi, 2020; Grange and Yau, 2020; Aksel and Imamoglu, 2020; Cho, 2020; Turkoglu et al , 2019; Gur et al , 2019; Maclean and Salama, 2019; Chen et al , 2019; Huang et al , 2018; Mohit and Azim, 2012; Dekker et al , 2011). The literature on the housing environment revealed location (Buys and Miller, 2012), easy to access (Wang and Wang, 2015; Ciorici and Dantzler, 2019), shopping center (Cao and Wang, 2016; Wang and Wang, 2015), parks and open spaces neighboring (Lee et al , 2016; Cao and Wang, 2016; Karacor and Parlar, 2017; Mouratidis, 2018; Grange and Yau, 2020), attractive appearance (Lee et al , 2016; Mouratidis, 2018; Grange and Yau, 2020), safety and security (Parkes et al , 2002; Buys and Miller, 2012; Wang and Wang, 2015; Lee et al , 2016; Mouratidis, 2018; Ciorici and Dantzler, 2019), housing size (Li et al , 2019; Huang and Du, 2015; Cho, 2020), housing quality (Ciorici and Dantzler, 2019; Cho, 2020), management and service (Cho, 2020) and social relations with neighbors (Berkoz and Kellekci, 2007; Grange and Yau, 2020) are the housing environment dimensions influencing residents’ satisfaction. Ibem and Alagbe (2015) revealed key dimensions of adequate housing, such as an ambient condition of interiors and adequacy of security, utilities and neighborhood facilities; social infrastructure; privacy and sizes of sleeping area in residence; and sizes of living and dining space at the Ogun State Southwest, Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%